Fungal Infections and Their Impact on Cytokine Dysregulation: Biomarkers of Inflammation in Histoplasma capsulatum Infections - Sadam Hameed Rasheed; Haneen Kadhim Zaid; Mustafa Kareem Hassan; Osama A. Mohsein (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Fungal infections remain a global health concern, particularly in immunocompromised individuals, due to their high morbidity and mortality rates. Specific Background: Among these, Histoplasma capsulatum causes histoplasmosis, a systemic mycosis marked by immune dysregulation and oxidative stress, yet the precise mechanisms linking cytokine imbalance and disease severity remain insufficiently understood. Knowledge Gap: Limited data exist on the concurrent assessment of pro- and anti-inflammatory cytokines and oxidative stress biomarkers in histoplasmosis, especially in non-endemic regions. Aims: This study aimed to evaluate cytokine and oxidative stress profiles in patients with H. capsulatum infection and determine their association with disease severity. Results: Compared to controls, patients exhibited elevated TNF-α, IL-6, IFN-γ, IL-10, TGF-β, CRP, and MDA levels, alongside reduced total antioxidant capacity (TAC), with biomarker levels increasing proportionally with disease severity (P < 0.001). Novelty: This is the first study to integrate immunological and oxidative biomarkers in H. capsulatum infection, revealing their interdependent role in pathogenesis. Implications: Findings highlight that simultaneous cytokine and oxidative stress dysregulation underpins disease progression, suggesting that biomarker monitoring could improve prognostic evaluation and guide targeted immunomodulatory therapies.Highlight : The study evaluates cytokine and oxidative stress biomarkers in histoplasmosis patients. Results show increased inflammatory markers correlated with disease severity. Biomarker monitoring may guide prognosis and improve therapeutic strategies. Keywords : Histoplasma capsulatum, cytokines, TNF-α, IL-6, IL-10